Study of Meningitis Inflammatory Disease among children admitted to Benghazi Pediatrics Hospital during 2017-2020 - Elshebani, Asma. B.; Elfaitouri , Amal. M.; Busaadia , Mariam. A. S.; alobadi , Abd Alraouf E.; Alhassi, Butgains A.; Alsaiti, Mayar. H.; Alatti, Mohamed. S.; Boujanah , Sondos. I. (Scientific Journal of University of Benghazi, 2022)
Background: Meningitis is an inflammation that affects the delicate membranes called meninges, which cover the brain and spinal cord. Meningitis occurs when fluid surrounding the meninges becomes infected. The most common causes of meningitis are viruses, bacteria, protozoa, fungi, and other agents. Aim: To investigate the epidemiological picture of meningitis in patients at Benghazi Pediatric Hospital. Methods: a descriptive cross-sectional study was conducted from 2017 – 2020. Results: The majority of meningitis cases were in males (59%) with females at 41%, while the majority of meningitis cases were in the age group of below 1 year (73.7%). The majority of patients according to the unit of admission, were from unit B (the cardiovascular unit) (25.9%) and the lowest was from the surgery unit (0.2%). In general, the majority of meningitis patients according to the year had an increase from 2017 (17.2%) to 2020 (24.6%). While meningitis occurring in patients according to months showed the highest incidence in July (13.8%) and August (12.8%), and according to the season in the summer (35.2%) and winter (14.2%). The distribution of patients according to the duration of disease was from 6 to 10 days (20.2%); the distribution of patients according to outcome in all years, the majority were discharged in good health (89.9 %). Conclusion: This study concluded that meningitis affected males more than females, and is common in children whose age is under one year. Meningitis is more common during July and August, showing more incidence in summer than winter.